Impact of Na+ and Ca2+ Cations on the Adsorption of H2S on Binder-Free LTA Zeolites - Annika Starke; Christoph Pasel; Christian Bläker; Tobias Eckardt; Jens Zimmermann; Dieter Bathen (Adsorption Science & Technology, 2021)
Hydrogen sulfide is removed from natural gas via adsorption on zeolites. The process operates very effectively, but there is still potential for improvement. Therefore, in this article, the adsorption of hydrogen sulfide was investigated on eight LTA zeolites with different cation compositions. Starting with the zeolite NaA (4 A), which contains only Na+ cations, the Ca2+ cation content was gradually increased by ion exchange. Equilibrium isotherms from cumulative breakthrough curve experiments in a fixed-bed adsorber at 25°C and 85°C at 1.3 bar (abs.) were determined in the trace range up to a concentration of 2000 ppmmol. From a comparison of the isotherms of the different materials, a mechanistic proposal for the adsorption is developed, taking into account the specific positions of the cations in the zeolite lattice when the degree of exchange is increased. The shape of the isotherms indicates two energetically different types of adsorption sites. It is assumed that two mechanisms are superimposed: a chemisorptive mechanism with dissociation of hydrogen sulfide and covalent bonding of the proton and the hydrogen sulfide ion to the zeolite lattice and a physisorptive mechanism by electrostatic interaction with the cations in the lattice. As the degree of exchange increases, the proportion of chemisorption sites seems to decrease. Above an exchange degree of 50%, only evidence of physisorption can be found. It is shown that this finding points to the involvement of weakly bound sodium cations at cation position III in the chemisorption of hydrogen sulfide.